Globalization and Food Sovereignty: Global and Local Change in the New Politics of Food - PETER ANDRÃ‰E, JEFFREY AYRES, MICHAEL J. BOSIA, MARIE-JOSÃ‰E MASSICOTTE (University of Toronto Press, 2014)
The evidence speaks for itself. If we turn to the world as a source of nutrition, we see the glaring paradox brought about by a globalizing food system that arose in the industrial and scientific transformation of food production in Europe and the United States and was then exported first to the most proximate agricultural economies, and in the past three decades, carried through a series of structural reforms to every region of the global South. The paradox is evident in a context of increasing food production and access to affordable food for many, especially in urban areas, that has brought land grabs and dislocations, hunger and food shortages, obesity, food contamination, and environmental impacts that threaten the very resources upon which that food production depends. This volume focuses on responses to these paradoxical crises, in which peasants and farmers, consumers and activists, and other social movement and economic actors are coalescing around a toolkit of participatory actions that are variously called â€œfood sovereigntyâ€ or â€œfood democracy.â€ We take the position that the geographically diverse food crises are interrelated and that they can be tied to McMichaelâ€™s concept of a â€œglobalizing food regimeâ€ (McMichael 2011, 805). This view emphasizes the intensification and expansion across borders of the industrial model of agriculture based on capital-intensive equipment, energy-intensive inputs of fertilizers, pesticides, water, and seeds, and favouring largescale production, often oriented towards export markets. Through increasingly concentrated and integrated processes from local producers to state regulations, large food conglomerates, and global distribution chains, this regime is the product of the historic and ongoing transformation of agriculture in Europe and North America, now dominated by a tiny number of major corporations in the seed, food processing, and distribution sectors. It is this globalizing food regime of production and distribution that these crises reveal as intensely problematic.